A kind of non-stick aluminum foil and preparation method thereof
By adding trace elements such as Si, Fe, Mg to the base layer of the aluminum foil, and applying food-grade methyl silicone oil and other materials to the surface, and punching holes, the problem of food adhesion to the aluminum foil during baking is solved, and food cleaning and nutritional maintenance are achieved.
Patent Information
- Application Number
- CN202411891199.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-04-04
AI Technical Summary
During the baking process, food is prone to stick to aluminum foil, resulting in juice loss, taste and nutritional value reduction, and at the same time affecting the reusability of aluminum foil.
A non-stick aluminum foil is used, and its base layer contains trace elements such as Si, Fe, Mg, etc., to improve the strength and corrosion resistance of the material; the surface coating consists of food-grade methyl silicone oil, catalyst, antibacterial agent and crosslinking agent, which has good heat resistance and chemical stability, and holes are punched on the surface to promote water vapor discharge.
Effectively prevent food from sticking to the packaging, facilitate the removal of food and the cleaning of packaging, maintain the taste and nutritional value of the food, and improve the reusability of aluminum foil.
Smart Images

Figure BDA0005200702910000111 
Figure BDA0005200702910000121
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of aluminum foil production, and in particular to a non-stick aluminum foil and a preparation method thereof. Background Art
[0002] Aluminum foil is a material that is directly rolled into thin sheets with a thickness of less than 0.3mm. It is light in weight, moderate in strength and low in cost. It is suitable as a wrapping material for grilled food. It can keep the food moist and prevent excessive evaporation of water during the grilling process. It can also reduce direct contact between food and the grill, avoid food sticking, and keep the grilled food clean and hygienic.
[0003] Household aluminum foil is usually made of deformed aluminum alloys such as 8011, 8021, 1235, etc. Its production process includes smelting and casting, hot rolling, cold rolling, intermediate annealing, longitudinal shearing, foil rolling, finished product slitting, finished product annealing, inspection and packaging. It is environmentally friendly, beautiful, moisture-proof, fresh-keeping, abrasion-resistant, non-toxic and odorless. It is widely used in aviation food, fast food, beverage packaging, daily necessities preservation and other fields.
[0004] When baking, use aluminum foil to wrap vegetables, potatoes, meat, etc. to prevent them from burning and producing carcinogens. When handling grilled food, the food is easy to stick to the aluminum foil, which not only causes the loss of food juice, but also affects the taste and nutritional value of the food, and reduces the reusability of the aluminum foil. Summary of the invention
[0005] In order to improve the problem that food easily adheres to aluminum foil when grilling food, the present application provides a non-stick aluminum foil and a preparation method thereof.
[0006] The present application provides a non-stick aluminum foil, which adopts the following technical solution: A non-stick aluminum foil comprises a base layer and a surface coating. The weight percentages of the raw materials in the base layer are as follows: Si 0.2-0.4%, Mg 0.06-0.09%, Fe 0.5-0.8%, Cr 0.1-0.15%, Cu 0.1-0.2%, Mn 0.03-0.08%, Ti 0.03-0.06%, and the balance is Al. The raw material components of the surface coating include the following raw materials: food-grade methyl silicone oil, a catalyst, an antibacterial agent, and a cross-linking agent. The surface of the non-stick aluminum foil is perforated, with 1-2 holes per square centimeter.
[0007] By adopting the above technical solution, the addition of Si, Fe and Mg in the base layer improves the strength of the material, the addition of Cu and Cr enhances the corrosion resistance of the material, and Ti and Mn help to refine the grains and improve the mechanical properties of the material. The addition of these trace elements can improve the processing performance of the material and the quality of the final product. A surface coating is applied on the surface of the aluminum foil. The surface coating has good heat resistance and chemical stability, so that it can remain stable during microwave heating, not easy to deform or release harmful substances. The surface coating can prevent food from adhering to the packaging, making it easier to take out the food and clean the packaging.
[0008] Food-grade methyl silicone oil has good chemical stability, electrical insulation and weather resistance, a wide range of viscosity, high transparency, no odor, good hydrophobicity, etc. As a surface coating for grilled food, food-grade methyl silicone oil can effectively prevent food from directly contacting charcoal during the grilling process, avoiding burning or the production of harmful substances. At the same time, its hydrophobicity can also reduce the loss of water on the surface of food and maintain the taste and nutritional value of food.
[0009] The catalyst promotes the chemical reaction between silane molecules, polymerizing them into longer chain structures, thereby increasing the molecular weight and viscosity of silicone oil. Antibacterial agents are used in the surface coating of grilled food to inhibit or kill bacteria. Cross-linking agents play a role in strengthening the connection between silicone oil molecules during the preparation of silicone oil, which can improve the strength and stability of silicone oil. The prepared surface coating effectively prevents food from burning or producing harmful substances during the grilling process, reduces the loss of water on the surface of food, and maintains the taste and nutritional value of food. Punching plays multiple roles such as promoting the discharge of water vapor, managing grease, transferring heat, and preventing the production of harmful substances. These effects together make the grilling process more efficient, healthy and delicious.
[0010] Preferably, one side of the surface coating is also coated with an outer layer, and the raw material components of the outer layer include the following raw materials in parts by weight: 20-30 parts of polypropylene, 10-15 parts of maleic anhydride grafted polypropylene, 5-8 parts of polyvinyl alcohol, 22-25 parts of modified plant fiber, 15-18 parts of modified montmorillonite, 2-3 parts of perilla seed oil, and 1-2 parts of sodium silicate.
[0011] By adopting the above technical scheme, polypropylene has high tensile strength, impact strength and bending strength, can be well bonded with aluminum foil, has good chemical stability and good thermal stability, and can be safely heated in a microwave oven. Maleic anhydride grafted polypropylene is used as a compatibilizer to make polypropylene and modified plant fiber, modified montmorillonite, and sodium silicate have good compatibility, and improve the interfacial bonding strength between the material and the aluminum foil; moreover, the addition of maleic anhydride grafted polypropylene can significantly improve the mechanical properties of polypropylene, such as tensile strength, impact strength and bending strength. Polyvinyl alcohol has good water solubility and biodegradability, and is mixed with polypropylene and maleic anhydride grafted polypropylene to improve the water solubility, biodegradability and mechanical properties of the material, and maleic anhydride grafted polypropylene improves the compatibility between polypropylene and polyvinyl alcohol, thereby improving the comprehensive performance of the material.
[0012] Modified plant fibers can improve the mechanical strength of polypropylene, such as tensile strength and tear resistance, while enhancing its toughness, making the film more durable and having better heat resistance; the compatibility of modified plant fibers with polypropylene is improved, which helps to improve the mechanical properties, water absorption, flow properties and thermal properties of the material. The modified plant fibers have a microporous structure, which makes the polypropylene film have better air-venting properties. The formation of micropores helps to release the steam in the package during heating, preventing the package from expanding or rupturing, while maintaining the taste and quality of the food. The layered structure of modified montmorillonite can effectively disperse stress, enhance the rigidity and toughness of the material, and significantly improve the tensile strength, elastic modulus and hardness of polypropylene composites. The high thermal stability of modified montmorillonite can improve the thermal stability of polypropylene composites, which helps to improve the performance in high temperature environments.
[0013] Modified plant fibers can be loaded on the surface and pores of modified montmorillonite to improve the mechanical properties, thermal stability and compatibility of modified montmorillonite. The addition of modified montmorillonite can change the microwave absorption characteristics of the film and achieve a more uniform or more efficient heating effect. Moreover, the high thermal stability of modified montmorillonite helps to improve the thermal stability of the film during microwave heating, reduce the risk of deformation or degradation of the film due to high temperature, and ensure the safe use of the film in a microwave oven. Perilla seed oil improves the flexibility and elasticity of polypropylene, making it less prone to brittle cracking at high temperatures, improves the impact resistance of polypropylene, and enables it to better absorb and disperse energy when impacted by external forces, reducing material damage. Sodium silicate has good mechanical properties and thermal stability, and can be loaded in the structure of modified montmorillonite to further improve the corresponding performance of modified montmorillonite.
[0014] Preferably, the method for preparing the modified plant fiber comprises the following steps: (1) dispersing the straw fiber in a sodium hydroxide solution, ultrasonically treating for 20-30 min, washing with water, and then dispersing the fiber in deionized water, adding a silane coupling agent, and stirring uniformly to obtain pretreated straw fiber; (2) Grinding the fly ash, dispersing it in an ethanol solution, adding sodium lignin sulfonate, stirring evenly, filtering, and drying at 60-70° C. for 2-3 hours to obtain pretreated fly ash; (3) Dispersing the pretreated straw fiber of step (1) in deionized water, adding the pretreated fly ash of step (2), stirring at a temperature of 80-85° C. for 1-2 h, adding modified lignin, continuing stirring, and drying to obtain modified plant fiber.
[0015] By adopting the above technical solution, the surface of the straw fiber is treated with sodium hydroxide to remove the wax and part of the lignin on the fiber surface, making the fiber finer, increasing the compatibility of the fiber with the polymer matrix, and mixing with the silane coupling agent to enhance the interaction between the fiber and the matrix through chemical bonding. The silane coupling agent forms a "bridging" effect between the fiber and the matrix, thereby improving the compatibility between the two.
[0016] Fly ash is dispersed in an ethanol solution, and sodium lignin sulfonate can improve the fluidity of fly ash, so that fly ash is evenly mixed with other components. Pretreated straw fiber is mixed with pretreated fly ash, and fly ash can be loaded on the surface of straw fiber to improve the mechanical properties of straw fiber such as tensile strength and toughness, and improve the thermal stability of straw fiber. The modified lignin has a certain viscosity, so that fly ash is tightly bonded to the surface of straw fiber, and the performance stability of straw fiber is improved. It is subsequently applied to film to improve the mechanical properties and thermal stability of the film, reduce thermal deformation, and increase the use temperature range and durability of the film.
[0017] Preferably, the mass ratio of the straw fiber, fly ash and modified lignin is 1:0.4-0.6:0.08-0.09.
[0018] By adopting the above technical scheme, the mass ratio of straw fiber, fly ash and modified lignin is further limited within a certain range. Fly ash contains components such as silicate and aluminate, which can improve the thermal stability of the film and reduce thermal deformation. Fly ash can be loaded on the surface and pores of straw fiber to improve the tensile strength and toughness of straw fiber. Modified lignin makes fly ash tightly bonded to the surface of straw fiber, improving the performance stability of straw fiber. There is a synergistic effect between straw fiber, fly ash and modified lignin, so that the modified straw fiber has better comprehensive performance, which can be subsequently applied to the film to improve the corresponding performance of the film.
[0019] Preferably, the preparation method of the modified lignin comprises the following steps: dispersing lignin in deionized water, ultrasonicating for 30-35 minutes, adding hydrogen peroxide, stirring for 2-3 hours, filtering, then dispersing in acetic acid solution, adding chitosan and nano-titanium dioxide, stirring evenly, and drying to obtain modified lignin.
[0020] By adopting the above technical scheme, lignin is first treated with hydrogen peroxide to improve the surface properties of lignin, so that the surface hydroxyl groups are oxidized to form groups that are more soluble in water, thereby improving the water solubility of lignin, and then dispersed in acetic acid solution, chitosan and nano-titanium dioxide are added, chitosan has a certain viscosity, and is mixed with lignin. There is a hydrogen bond between chitosan and lignin to form a network structure, which improves the mechanical properties and viscosity of the system. Nano-titanium dioxide can be embedded in the network structure formed by chitosan and lignin, and improve the tensile properties and other mechanical properties of the system. It is subsequently applied to straw fibers, so that the various components in the straw fibers are tightly bonded, and the comprehensive properties of the film are improved. In addition, both chitosan and nano-titanium dioxide have antibacterial properties. The addition of lignin can further enhance the antibacterial effect of the system, which helps to subsequently improve the antibacterial properties of the film.
[0021] Preferably, the mass ratio of the lignin, chitosan and nano-titanium dioxide is 1:0.1-0.2:0.3-0.5.
[0022] By adopting the above technical scheme, the mass ratio of lignin, chitosan and nano-titanium dioxide is further limited within a certain range, the viscosity and mechanical properties of lignin are improved, which is helpful for subsequent application in straw fibers and improving the adhesion between the various components in the straw fibers. The mixture of lignin and chitosan improves the mechanical properties of the film, such as tensile strength and storage modulus, and the addition of nano-titanium dioxide further enhances the thermal stability of the material. In addition, the composite of lignin, chitosan and nano-titanium dioxide can produce a synergistic effect, improve the antibacterial durability and use efficiency of the material, and help to subsequently improve the corresponding performance of the film.
[0023] Preferably, the preparation method of the modified montmorillonite comprises the following steps: (1) dispersing montmorillonite in deionized water, adding sodium chloride, stirring at a temperature of 50-55° C. for 1-2 hours, filtering, and drying to obtain pretreated montmorillonite; (2) dispersing graphene in a DMF solution, adding bamboo charcoal fiber, stirring at 80-85° C. for 1-2 h, filtering, and drying to obtain pretreated graphene; (3) dispersing the pretreated montmorillonite in step (1) in deionized water, adding the pretreated graphene and modified carboxymethyl cellulose in step (2), stirring at a temperature of 80-85° C. for 1-2 h, and drying to obtain modified montmorillonite.
[0024] By adopting the above technical solution, sodium chloride can be inserted into the interlayer of natural montmorillonite and subjected to sodium-based treatment. The thermal stability of the modified montmorillonite is enhanced and the interlayer spacing is increased, which is beneficial to the subsequent modification of the montmorillonite.
[0025] Graphene has good mechanical properties, thermal conductivity and flexibility, and bamboo charcoal fiber has good air permeability and toughness. Graphene can be loaded on the surface of bamboo charcoal fiber to improve the thermal conductivity, chemical resistance and heat resistance of bamboo charcoal fiber. When heated, it can quickly absorb microwave energy and convert it into thermal energy, achieving rapid heating, more uniform heat distribution, and avoiding local overheating.
[0026] Pretreated montmorillonite, pretreated graphene and modified carboxymethyl cellulose are mixed. Graphene can be loaded on the surface of montmorillonite. The modified carboxymethyl cellulose has a certain viscosity, so that the graphene adheres to the surface of montmorillonite, thereby improving the mechanical properties, thermal conductivity and thermal stability of montmorillonite. It is subsequently applied to thin films to improve the comprehensive performance of the films.
[0027] Preferably, the mass ratio of the montmorillonite, graphene and modified carboxymethyl cellulose is 1g:30-40mg:0.2-0.3g.
[0028] By adopting the above technical solution, the mass ratio of montmorillonite, graphene and modified carboxymethyl cellulose is further limited, so that montmorillonite has good thermal stability, graphene and bamboo charcoal fiber have good thermal conductivity, and when used for food heating packaging, they can quickly absorb microwave or electromagnetic energy and convert it into heat energy to achieve rapid heating of food. At the same time, due to the distribution of graphene and bamboo charcoal fiber, the heat distribution is more uniform, avoiding local overheating and ensuring the uniformity of food heating. The composite of graphene and bamboo charcoal fiber can improve the chemical and thermal stability of the film, and the modified carboxymethyl cellulose allows the graphene to adhere to the surface of montmorillonite, so that it can still maintain its performance in a heating environment, avoiding the material from decomposing or releasing harmful substances at high temperatures, and ensuring the safety and stability of food heating packaging.
[0029] Preferably, the preparation method of the modified carboxymethyl cellulose comprises the following steps: dispersing the carboxymethyl cellulose in a NaOH solution, stirring, filtering, and then dispersing in deionized water, adding starch and nano-silver particles, stirring evenly, and drying to obtain the modified carboxymethyl cellulose.
[0030] By adopting the above technical solution, when carboxymethyl cellulose is dissolved in water, its molecular chains will form a network structure through hydrogen bond interactions, thereby increasing the viscosity of the solution. The presence of NaOH can further promote the dispersion and dissolution of the carboxymethyl cellulose molecular chains and increase the viscosity of the solution.
[0031] Starch and carboxymethyl cellulose form physical crosslinks through hydrogen bonds to enhance the mechanical properties, viscosity and stability of the material. Nanosilver particles are embedded in the structure of the crosslinked system to further enhance the mechanical properties and antibacterial properties of the system. Carboxymethyl cellulose and starch, as polymers with good biocompatibility, can be used as carriers of nanosilver particles to form a stable composite material, thereby improving the durability and safety of antibacterial activity. The mixture of carboxymethyl cellulose, starch and nanosilver particles improves the antibacterial properties and mechanical strength of the film.
[0032] In a second aspect, the present application also provides a method for preparing a non-stick aluminum foil, comprising the following steps: (1) uniformly mixing the raw materials in the base layer, smelting and refining to form an ingot; (2) hot rolling the ingot at 520-530° C. to obtain a hot rolled coil; (3) cold rolling the hot-rolled coil until the coil is rolled to a thickness of 2.0-2.5 mm to obtain a cold-rolled billet; (4) keeping the cold-rolled billet at 570-580° C. for 22-23 hours, cooling to room temperature, and continuing cold rolling to a thickness of 0.1-0.2 mm, keeping at 360-370° C. for 10-11 hours, trimming, and annealing at 180-190° C. for 25-28 hours to obtain a finished aluminum foil; (5) Mix food-grade methyl silicone oil, a catalyst, an antibacterial agent and a cross-linking agent, stir evenly at a temperature of 70-75° C., and evenly coat the mixture on the surface of the finished aluminum foil in step (4) at a coating amount of 1-1.5 g / m2. The speed of the coating machine is 60-80 m / min. The mixture is dried at a temperature of 185-200° C., and evenly distributed small holes are pierced through the non-stick aluminum foil, with a hole diameter of 1-6 mm, to obtain a non-stick aluminum foil.
[0033] By adopting the above technical scheme and the above preparation method, the operation is simple and the process time is short, which helps to improve the mechanical properties and production efficiency of the non-stick aluminum foil. The obtained non-stick aluminum foil has good mechanical properties and antibacterial properties.
[0034] Preferably, when one side of the surface coating is also coated with an outer layer, the method for preparing the non-stick aluminum foil further includes the following steps: after step (5), the raw material components of the outer layer are mixed evenly at a temperature of 170-180°C, granulated, blown into a film, and then hot-pressed onto the surface coating, and punched with holes with a diameter of 1-6 mm to obtain a non-stick aluminum foil.
[0035] In summary, this application has the following beneficial effects: 1. In the present application, a surface coating is applied on the surface of the aluminum foil. The surface coating has good heat resistance and chemical stability, so that it can remain stable during microwave heating and is not easy to deform or release harmful substances. The surface coating can prevent food from adhering to the packaging, making it easier to take out the food and clean the packaging.
[0036] 2. The modified plant fiber in this application can improve the mechanical strength of polypropylene, such as tensile strength and tear resistance, while enhancing its toughness, making the film more durable and having better heat resistance; the compatibility of the modified plant fiber with polypropylene is improved, which helps to improve the mechanical properties, water absorption properties, flow properties and thermal properties of the material.
[0037] 3. The layered structure of the modified montmorillonite in this application can effectively disperse stress, enhance the rigidity and toughness of the material, and significantly improve the tensile strength, elastic modulus and hardness of the polypropylene composite material. The high thermal stability of the modified montmorillonite can improve the thermal stability of the polypropylene composite material, which is helpful for its performance in high temperature environments. DETAILED DESCRIPTION
[0038] The present application is further described in detail below with reference to the embodiments.
[0039] The raw materials used in the examples and comparative examples can all be obtained commercially.
[0040] Preparation example of modified plant fiber Preparation Example 1-1 The preparation method of modified plant fiber comprises the following steps: (1) 1.2 kg of straw fiber was dispersed in 2 L of 10% sodium hydroxide solution, ultrasonicated for 25 min, washed with water, and then dispersed in 2.5 L of deionized water, 0.2 kg of silane coupling agent KH-550 was added, and stirred evenly to obtain pretreated straw fiber; (2) Grinding the fly ash, dispersing it in 1.5 L of ethanol solution, adding 0.08 kg of sodium lignin sulfonate, stirring evenly, filtering, and drying at 66 ° C for 2.5 h to obtain pretreated fly ash; (3) The pretreated straw fiber of step (1) is dispersed in 3.5 L of deionized water, and the pretreated fly ash of step (2) is added, and stirred at a temperature of 85° C. for 2 h. The modified lignin is added, and the stirring is continued for 2 h. The modified plant fiber is dried to obtain the modified plant fiber.
[0041] The mass ratio of straw fiber, fly ash and modified lignin is 1:0.6:0.08.
[0042] The preparation method of modified lignin comprises the following steps: dispersing 0.7 kg of lignin in 1.3 L of deionized water, ultrasonicating for 35 min, adding 0.1 kg of 20% hydrogen peroxide, stirring for 2.5 h, filtering, and then dispersing in 1.5 L of 10% acetic acid solution, adding chitosan and nano titanium dioxide, stirring for 2 h, and drying to obtain modified lignin.
[0043] The mass ratio of lignin, chitosan and nano-titanium dioxide is 1:0.1:0.5.
[0044] Preparation Example 1-2 The difference from Preparation Example 1-1 is that in step (2), fly ash is not added.
[0045] Preparation Example 1-3 The difference from Preparation Example 1-1 is that in step (3), no modified lignin is added.
[0046] Preparation Example 1-4 The difference from Preparation Example 1-1 is that the mass ratio of straw fiber, fly ash and modified lignin is 1:0.4:0.09.
[0047] Preparation Example 1-5 The difference from Preparation Example 1-1 is that the mass ratio of straw fiber, fly ash and modified lignin is 1:0.1:0.13.
[0048] Preparation Example 1-6 The difference from Preparation Example 1-1 is that chitosan is not added in the preparation method of the modified lignin.
[0049] Preparation Example 1-7 The difference from Preparation Example 1-1 is that in the preparation method of the modified lignin, no nano titanium dioxide is added.
[0050] Preparation Example 1-8 The difference from Preparation Example 1-1 is that in the preparation method of modified lignin, the mass ratio of lignin, chitosan and nano-titanium dioxide is 1:0.2:0.3.
[0051] Preparation Example 1-9 The difference from Preparation Example 1-1 is that in the preparation method of modified lignin, the mass ratio of lignin, chitosan and nano-titanium dioxide is 1:0.5:0.1.
[0052] Preparation example of modified montmorillonite Preparation Example 2-1 The preparation method of modified montmorillonite comprises the following steps: (1) Dispersing 1.5 kg of montmorillonite in 2 L of deionized water, adding 0.2 kg of sodium chloride, stirring at 55 ° C for 2 h, filtering, and drying to obtain pretreated montmorillonite; (2) dispersing graphene in 0.8 L DMF solution, adding 0.06 kg bamboo charcoal fiber, stirring at 85 ° C for 2 h, filtering, and drying to obtain pretreated graphene; (3) Dispersing the pretreated montmorillonite in step (1) in 4 L of deionized water, adding the pretreated graphene and modified carboxymethyl cellulose in step (2), stirring at 85° C. for 2 h, and drying to obtain modified montmorillonite.
[0053] The mass ratio of montmorillonite, graphene and modified carboxymethyl cellulose is 1g:30mg:0.3g.
[0054] The preparation method of modified carboxymethyl cellulose comprises the following steps: dispersing 1 kg of carboxymethyl cellulose in 2 L of NaOH solution with a mass fraction of 12%, stirring for 1 hour, filtering, and then dispersing in 2 L of deionized water, adding 0.09 kg of starch and 0.2 kg of nano silver particles, stirring evenly, and drying to obtain modified carboxymethyl cellulose.
[0055] Preparation Example 2-2 The difference from Preparation Example 2-1 is that in step (2), no graphene is added.
[0056] Preparation Example 2-3 The difference from Preparation Example 2-1 is that in step (3), modified carboxymethyl cellulose is not added.
[0057] Preparation Example 2-4 The difference from Preparation Example 2-1 is that the mass ratio of montmorillonite, graphene and modified carboxymethyl cellulose is 1 g:40 mg:0.2 g.
[0058] Preparation Example 2-5 The difference from Preparation Example 2-1 is that the mass ratio of montmorillonite, graphene and modified carboxymethyl cellulose is 1 g:20 mg:0.5 g.
[0059] Preparation Example 2-6 The difference from Preparation Example 2-1 is that starch is not added in the preparation method of modified carboxymethyl cellulose.
[0060] Preparation Example 2-7 The difference from Preparation Example 2-1 is that in the preparation method of modified carboxymethyl cellulose, no nano silver particles are added. Example
[0061] Example 1 A non-stick aluminum foil comprises a base layer and a surface coating, wherein the base layer weighs 1 kg, and the weight percentages of the raw materials in the base layer are as follows: 0.2% Si, 0.06% Mg, 0.5% Fe, 0.1% Cr, 0.1% Cu, 0.03% Mn, 0.03% Ti, and the balance is Al; the raw material components of the surface coating comprise the following raw materials: 10 kg food-grade methyl silicone oil, 2 kg catalyst, and 3 kg cross-linking agent; holes are punched on the surface of the non-stick aluminum foil, with one hole punched per square centimeter; the food-grade methyl silicone oil is food-grade polydimethylsiloxane purchased from Foshan Guirunbao Biotechnology Co., Ltd.; the catalyst is dibutyltin dilaurate, the cross-linking agent is methyltributylidene oxime silane, and the antibacterial agent is nano silver particles.
[0062] Use a punching machine to pierce evenly distributed small holes in the non-stick aluminum foil, and the diameter of the holes is 2mm.
[0063] The method for preparing the non-stick aluminum foil comprises the following steps: (1) uniformly mixing the raw materials in the base layer, smelting and refining to form an ingot; (2) hot rolling the ingot at 530° C. to obtain a hot rolled coil; (3) cold rolling the hot-rolled coil until the coil is rolled to a thickness of 2.2 mm to obtain a cold-rolled billet; (4) keeping the cold-rolled billet at 580° C. for 22 h, cooling it to room temperature, and continuing to cold-roll it to a thickness of 0.2 mm, keeping it at 370° C. for 10 h, trimming it, and annealing it at 190° C. for 28 h to obtain a finished aluminum foil; (5) Mix food-grade methyl silicone oil, a catalyst and a cross-linking agent, stir evenly at a temperature of 75° C., and evenly coat the mixture on the surface of the finished aluminum foil in step (4). The coating amount is 1.5 g / m2, the speed of the coating machine is 70 m / min, and the mixture is dried at a temperature of 190° C. to obtain a non-stick aluminum foil.
[0064] Example 2 A non-stick aluminum foil, which differs from Example 1 in that one side of the surface coating is also coated with an outer layer, and the raw material components of the outer layer include the following raw materials by weight: 20 kg of polypropylene, 10 kg of maleic anhydride grafted polypropylene, 5 kg of polyvinyl alcohol, 25 kg of modified plant fiber, 15 kg of modified montmorillonite, 2 kg of perilla seed oil, and 1 kg of sodium silicate.
[0065] When one side of the surface coating is also coated with an outer layer, the method for preparing the non-stick aluminum foil further includes the following steps: after step (5), the raw material components of the outer layer are mixed evenly at a temperature of 180° C., granulated, blown into a film, and then hot-pressed and bonded to the finished aluminum foil to obtain the non-stick aluminum foil.
[0066] Granulation obtains pellets, the length-diameter ratio of the single-screw extruder is 20:1, the head temperature of the single-screw extruder is 110°C, the die head temperature is 118°C, the barrel temperature is 57°C in the first stage, 100°C in the second stage, and 120°C in the third stage; The barrel temperature of the electromagnetic dynamic extruder used for blow molding film is 130℃ for the first stage, 135℃ for the second stage, and 140℃ for the third stage. The die head temperature of the electromagnetic dynamic extruder is 110℃, and the die head temperature of the electromagnetic dynamic extruder is 105℃. The temperature of the thermocompression bonding was 250°C and the pressure was 45 kg.
[0067] The modified plant fiber was prepared by using Preparation Example 1-1; and the modified montmorillonite was prepared by using Preparation Example 2-1.
[0068] Example 3 A non-stick aluminum foil, which differs from Example 2 in that the weight percentages of the raw materials in the base layer are as follows: Si 0.4%, Mg 0.09%, Fe 0.8%, Cr 0.15%, Cu 0.2%, Mn 0.08%, Ti 0.06%, and the balance is Al; The raw material components of the outer layer include the following raw materials by weight: 30 kg polypropylene, 15 kg maleic anhydride grafted polypropylene, 8 kg polyvinyl alcohol, 22 kg modified plant fiber, 18 kg modified montmorillonite, 3 kg perilla seed oil, and 2 kg sodium silicate.
[0069] Example 4 A non-stick aluminum foil, which is different from Example 2 in that the modified plant fiber is prepared using Preparation Example 1-2.
[0070] Example 5 A non-stick aluminum foil, which is different from Example 2 in that the modified plant fiber is prepared using Preparation Examples 1-3.
[0071] Example 6 A non-stick aluminum foil, which is different from Example 2 in that the modified plant fiber is prepared using Preparation Examples 1-4.
[0072] Example 7 A non-stick aluminum foil, which is different from Example 2 in that the modified plant fiber is prepared using Preparation Examples 1-5.
[0073] Example 8 A non-stick aluminum foil, which is different from Example 2 in that the modified plant fiber is prepared using Preparation Examples 1-6.
[0074] Example 9 A non-stick aluminum foil, which is different from Example 2 in that the modified plant fiber is prepared using Preparation Examples 1-7.
[0075] Example 10 A non-stick aluminum foil, which is different from Example 2 in that the modified plant fiber is prepared using Preparation Examples 1-8.
[0076] Embodiment 11 A non-stick aluminum foil, which is different from Example 2 in that the modified plant fiber is prepared using Preparation Examples 1-9.
[0077] Example 12 A non-stick aluminum foil, which is different from Example 2 in that the modified montmorillonite is prepared using Preparation Example 2-2.
[0078] Embodiment 13 A non-stick aluminum foil, which is different from Example 2 in that the modified montmorillonite is prepared using Preparation Example 2-3.
[0079] Embodiment 14 A non-stick aluminum foil, which is different from Example 2 in that the modified montmorillonite is prepared using Preparation Example 2-4.
[0080] Embodiment 15 A non-stick aluminum foil, which is different from Example 2 in that the modified montmorillonite is prepared using Preparation Example 2-5.
[0081] Example 16 A non-stick aluminum foil, which is different from Example 2 in that the modified montmorillonite is prepared using Preparation Example 2-6.
[0082] Embodiment 17 A non-stick aluminum foil, which is different from Example 2 in that the modified montmorillonite is prepared using Preparation Example 2-7.
[0083] Comparative Example Comparative Example 1 A non-stick aluminum foil, which is different from Example 2 in that no modified plant fiber is added.
[0084] Comparative Example 2 A non-stick aluminum foil, which is different from Example 2 in that the modified plant fiber is replaced by an equal amount of plant fiber.
[0085] Comparative Example 3 A non-stick aluminum foil, which is different from Example 2 in that modified montmorillonite is not added.
[0086] Comparative Example 4 A non-stick aluminum foil, which is different from Example 2 in that the modified montmorillonite is replaced by an equal amount of montmorillonite.
[0087] Performance testing The non-stick aluminum foils prepared in Examples 1-17 and Comparative Examples 1-4 were subjected to performance tests. Adhesion performance test: The adhesion of the prepared non-stick aluminum foil film was tested according to GB / 9286-98, wherein the film adhesion performance test includes indoor hanging test and film scratch test.
[0088] Surface tension performance test: The surface tension coefficient is measured by a dyne pen to determine the surface tension value of the non-stick aluminum foil.
[0089] Antibacterial performance test: The antibacterial performance of the prepared non-stick aluminum foil was tested in accordance with GB / T 31402-2015; Adhesion test: Wrap the meat with non-stick aluminum foil and heat it in an oven at 200°C for 30 minutes to test the adhesion between the non-stick aluminum foil and the meat, with the grades of 0 (completely non-stick), 1 (slight adhesion), 2 (moderate adhesion) and 3 (severe adhesion). The test results are shown in Table 1.
[0090] Table 1 Test data of embodiments and comparative examples It can be seen from Table 1 that the non-stick aluminum foil prepared in Example 1 of the present application has good adhesion, surface tension, antibacterial and adhesion. Among them, the indoor hanging sheet of Example 1 has no change for 50 days, the adhesion is level 1, the dyne value is 60, the Escherichia coli is 98.9%, the Staphylococcus aureus is 99.1%, and the adhesion is level 1, indicating that the prepared non-stick aluminum foil can prevent food from adhering to the packaging, has good mechanical properties, is not easy to tear, and has high antibacterial properties.
[0091] It can be seen from Table 1 that the non-stick aluminum foil prepared in Examples 2-3 of the present application has good adhesion, surface tension, antibacterial and adhesion. Among them, the indoor hanging sheet of Example 2 has no change for 60 days, the adhesion is level 0, the dyne value is 72, the Escherichia coli is 99.5%, the Staphylococcus aureus is 99.7%, and the adhesion is level 0, indicating that the prepared non-stick aluminum foil can prevent food from adhering to the packaging, has good mechanical properties, is not easy to tear, and has high antibacterial properties.
[0092] In Example 4, the preparation method of modified plant fiber does not add fly ash, and in Example 5, the preparation method of modified plant fiber does not add modified lignin. In Examples 6-7, the mass ratio of straw fiber, fly ash and modified lignin is changed. As can be seen from Table 1, the indoor hanging days of Examples 4-5 are significantly reduced, the film gridding and adhesion levels are level 1, the dyne value, Escherichia coli, and Staphylococcus aureus are all reduced, and the various performances of Example 7 are better than those of Examples 4-5, but worse than those of Examples 2-3 and Example 6, indicating that fly ash contains components such as silicates and aluminates, which improve the thermal stability of the film and reduce thermal deformation. Fly ash can be loaded on the surface and pores of straw fiber, and the tensile strength and toughness of straw fiber are improved. The modified lignin makes the fly ash tightly adhere to the surface of the straw fiber, improves the performance stability, antibacterial property, and adhesion of the straw fiber, so that the modified straw fiber has better comprehensive performance, which is subsequently applied to the film to improve the corresponding performance of the film.
[0093] In Example 8, the preparation method of modified lignin does not add chitosan, in Example 9, the preparation method of modified lignin does not add nano-titanium dioxide, and in Examples 10-11, the mass ratio of lignin, chitosan and nano-titanium dioxide is changed. As can be seen from Table 1, the indoor hanging days of Examples 8-9 increase, and the dyne value, Escherichia coli and Staphylococcus aureus all increase. The various properties of Example 11 are better than those of Examples 8-9, but worse than those of Examples 2-3 and Example 10, indicating that the mixture of lignin and chitosan improves the mechanical properties of the film, and the addition of nano-titanium dioxide further enhances the thermal stability of the material. The composite of lignin, chitosan and nano-titanium dioxide improves the antibacterial durability and adhesion of the material, which helps to subsequently improve the corresponding properties of the film.
[0094] In Example 12, the preparation method of modified montmorillonite does not add graphene, and in Example 13, the preparation method of modified montmorillonite does not add modified carboxymethyl cellulose. In Examples 14-15, the mass ratio of montmorillonite, graphene and modified carboxymethyl cellulose is changed. As can be seen from Table 1, the indoor hanging days of Examples 12-13 are significantly reduced, the film gridding and adhesion level are level 1, the dyne value, Escherichia coli and Staphylococcus aureus are all reduced, and the various performances of Example 15 are better than those of Examples 12-13, but worse than those of Examples 2-3 and Example 14, indicating that graphene improves the chemical and thermal stability of the film, and the modified carboxymethyl cellulose allows the graphene to adhere to the surface of montmorillonite, thereby improving the comprehensive properties of the film such as mechanical properties and adhesion.
[0095] The preparation method of modified carboxymethyl cellulose in Example 16 does not add starch, and the preparation method of modified carboxymethyl cellulose in Example 17 does not add nanosilver particles. It can be seen from Table 1 that the indoor hanging days of Examples 16-17 increase, the dyne value, Escherichia coli, and Staphylococcus aureus all increase, but the performance is worse than that of Examples 2-3, indicating that carboxymethyl cellulose and starch, as polymers with good biocompatibility, can be used as carriers of nanosilver particles to improve the durability and safety of antibacterial activity, and the mixture of carboxymethyl cellulose, starch and nanosilver particles improves the antibacterial property and mechanical strength of the film.
[0096] In Comparative Example 1 and Comparative Example 3, modified plant fiber and modified montmorillonite are not added respectively. As can be seen from Table 1, the indoor hanging days of Comparative Example 1 and Comparative Example 3 are significantly reduced, the film scratching and adhesion levels are level 3, and the dyne value, Escherichia coli and Staphylococcus aureus are all reduced, indicating that modified plant fiber and modified montmorillonite can improve the mechanical strength, antibacterial and adhesion of the film, so that the non-stick aluminum foil has better durability.
[0097] In Comparative Examples 2 and 4, the modified plant fiber is replaced by an equal amount of plant fiber, and the modified montmorillonite is replaced by an equal amount of montmorillonite. It can be seen from Table 1 that the test results of various properties of Comparative Examples 2 and 4 are significantly worse than those of Examples 2-3, but better than those of Comparative Examples 1 and 3, indicating that the modified plant fiber and modified montmorillonite in the present application have good mechanical properties, antibacterial properties and adhesion, thereby improving the corresponding properties of the film and improving the structural strength, antibacterial properties, adhesion and stability of the non-stick aluminum foil.
[0098] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A non-stick aluminum foil, characterized in that: The invention comprises a base layer and a surface coating, wherein the weight percentages of the raw materials in the base layer are as follows: Si 0.2-0.4%, Mg 0.06-0.09%, Fe 0.5-0.8%, Cr 0.1-0.15%, Cu 0.1-0.2%, Mn 0.03-0.08%, Ti 0.03-0.06%, and the balance is Al; the raw material components of the surface coating comprise the following raw materials: food-grade methyl silicone oil, a catalyst, an antibacterial agent and a cross-linking agent; and holes are punched on the surface of the non-stick aluminum foil, with 1-2 holes punched per square centimeter.
2. The non-stick aluminum foil according to claim 1, characterized in that: One side of the surface coating is also coated with an outer layer, and the raw material components of the outer layer include the following raw materials in parts by weight: 20-30 parts of polypropylene, 10-15 parts of maleic anhydride grafted polypropylene, 5-8 parts of polyvinyl alcohol, 22-25 parts of modified plant fiber, 15-18 parts of modified montmorillonite, 2-3 parts of perilla seed oil, and 1-2 parts of sodium silicate.
3. The non-stick aluminum foil according to claim 2, characterized in that: The preparation method of the modified plant fiber comprises the following steps: (1) dispersing the straw fiber in a sodium hydroxide solution, ultrasonicating for 20-30 min, washing with water, and then dispersing it in deionized water, adding a silane coupling agent, and stirring evenly to obtain pretreated straw fiber; (2) Grinding the fly ash, dispersing it in an ethanol solution, adding sodium lignin sulfonate, stirring evenly, filtering, and drying at 60-70° C. for 2-3 hours to obtain pretreated fly ash; (3) Dispersing the pretreated straw fiber in step (1) in deionized water, adding the pretreated fly ash in step (2), stirring at a temperature of 80-85° C. for 1-2 h, adding modified lignin, continuing to stir, and drying to obtain modified plant fiber.
4. The non-stick aluminum foil according to claim 3, characterized in that: The mass ratio of the straw fiber, fly ash and modified lignin is 1:0.4-0.6:0.08-0.
09.
5. The non-stick aluminum foil according to claim 3, characterized in that: The preparation method of the modified lignin comprises the following steps: dispersing the lignin in deionized water, ultrasonicating for 30-35 minutes, adding hydrogen peroxide, stirring for 2-3 hours, filtering, then dispersing in acetic acid solution, adding chitosan and nano titanium dioxide, stirring evenly, and drying to obtain the modified lignin.
6. The non-stick aluminum foil according to claim 5, characterized in that: The mass ratio of the lignin, chitosan and nano-titanium dioxide is 1:0.1-0.2:0.3-0.
5.
7. The non-stick aluminum foil according to claim 2, characterized in that: The preparation method of the modified montmorillonite comprises the following steps: (1) Dispersing montmorillonite in deionized water, adding sodium chloride, stirring at a temperature of 50-55°C for 1-2 hours, filtering, and drying to obtain pretreated montmorillonite; (2) dispersing graphene in DMF solution, adding bamboo charcoal fiber, stirring at 80-85° C. for 1-2 h, filtering, and drying to obtain pretreated graphene; (3) Dispersing the pretreated montmorillonite in step (1) in deionized water, adding the pretreated graphene and modified carboxymethyl cellulose in step (2), stirring at a temperature of 80-85° C. for 1-2 h, and drying to obtain modified montmorillonite.
8. The non-stick aluminum foil according to claim 7, characterized in that: The mass ratio of the montmorillonite, graphene and modified carboxymethyl cellulose is 1g:30-40mg:0.2-0.3g.
9. The non-stick aluminum foil according to claim 7, characterized in that: The preparation method of the modified carboxymethyl cellulose comprises the following steps: dispersing the carboxymethyl cellulose in a NaOH solution, stirring, filtering, and then dispersing the carboxymethyl cellulose in deionized water, adding starch and nano silver particles, stirring evenly, and drying to obtain the modified carboxymethyl cellulose.
10. The method for preparing a non-stick aluminum foil according to claim 1, characterized in that: The steps include: (1) Mix the raw materials in the base layer evenly, and then smelt and refine them to form an ingot; (2) hot rolling the ingot at 520-530° C. to obtain a hot rolled coil; (3) cold rolling the hot-rolled coil until the coil is rolled to a thickness of 2.0-2.5 mm to obtain a cold-rolled billet; (4) keeping the cold-rolled billet at 570-580°C for 22-23 hours, cooling to room temperature, and continuing cold rolling to a thickness of 0.1-0.2 mm, keeping at 360-370°C for 10-11 hours, trimming, and annealing at 180-190°C for 25-28 hours to obtain a finished aluminum foil; (5) Food-grade methyl silicone oil, catalyst, antibacterial agent and cross-linking agent are mixed, stirred evenly at a temperature of 70-75°C, and evenly coated on the surface of the finished aluminum foil in step (4), with a coating amount of 1-1.5 g / ㎡, a coating machine speed of 60-80 m / min, and dried at a temperature of 185-200°C. Evenly distributed small holes with a hole diameter of 1-6 mm are pierced on the non-stick aluminum foil to obtain a non-stick aluminum foil.
Citation Information
Cited By
Aluminum foil for lithium ion battery and cast rolling production method of aluminum foil
CN120485602A